Development of cell culture from liver and kidney of Indian major carp, Labeo rohita (Hamilton) - Lakra, W S; Behera, M R; Sivakumar, N; Goswami, M; Bhonde, R R (Indian Journal of Fisheries, 2011)
The present study was undertaken to assess the potential of six tissues of Labeo rohita viz. kidney, liver, heart, gill, caudal fin and swim bladder for attachment, cell outgrowth and proliferation by explant culture and trypusinization methods. Cell outgrowth was obtained from liver explants of L. rohita (2 months old) on ninth day. Cells radiated from liver explants grew and gave rise to colonies of individual cells. The disaggregated cells prepared by trypsinization of kidney tissue reached confluent stage nine days after seeding. The optimum incubation temperature for the liver and kidney cells was found to be 26-28ÂºC. Among the various media [Leibovitz-15 (L-15), M- 199 and EMEM] tested, L-15 was found to be most suitable for the attachment and cell proliferation. The media were supplemented with 15 % foetal bovine serum, 10 % fish muscle extract (FME) and 1 % fish (L. rohita) serum. Different pH of the growth media ranging from 7.2 to 7.8 was employed to determine optimum values. It was found that pH 7.4 proved to be the best for growth of cells.